Pathogen-induced dormancy in liquid limits gastrointestinal colonization of Caenorhabditis elegans - Liyang Zhang; Vyshnavi Gade; Natalia V. Kirienko (Virulence)
Colonization is generally considered a prerequisite for infection, but this event is context-dependent, as evidenced by the differing ability of the human pathogen Pseudomonas aeruginosa to efficiently colonize Caenorhabditis elegans on agar but not in liquid . In this study, we examined the impact of the environment, pathogen, host, and their interactions on host colonization. We found that the transition to a liquid environment reduces food uptake by about two-fold. Also expression of specific adhesins was significantly altered in liquid-based assays for P. aeruginosa, suggesting that it may be one factor driving diminished colonization. Unexpectedly, host immune pathways did not appear to play a significant role in decreased colonization in liquid. Although knocking down key immune pathways (e.g. daf-16 or zip-2), either alone or in combination, significantly reduced survival, the changes in colonization were very small. In spite of the limited bacterial accumulation in the liquid setting, pathogenic colonization was still required for the virulence of Enterococcus faecalis. In addition, we found that a pathogen-induced dormancy was displayed by C. elegans in liquid medium after pathogen exposure, resulting in cessation of pharyngeal pumping and a decrease in bacterial intake. We conclude that poor colonization in liquid is likely due to a combination of environmental factors and host-pathogen interactions. These results provide new insights into mechanisms for colonization in different models, enabling pathogenesis models to be fine-tuned to more accurately represent the conditions seen in human infections so that new tools for curbing bacterial and fungal infections can be developed.